Application Of Optimization Of Sunco Cooking Oil Planning In Alfamidi Minimarket Using Tsukamoto Method - Mochamad Andre Firdiansyah; Boy Isma Putra (Universitas Muhammadiyah Sidoarjo, 2021)
Alfamidi is a minimarket that sells fresh good products, frozen food processed meat that is needed by the public. An example of the product under study was in the form of 2 liter packaged sunco cooking oil. This study aims to predict the stock of goods not in line with sales of goods because customer demand is not always the same or uncertain for each item. Therefore it is necessary to predict the addition of stock of goods so that the addition of stock of goods is more in line with sales of goods. The step to solve this problem in this research is by using the Tsukamoto method the optimum value of the 2-liter packaged SunCo cooking oil product supply can be obtained. The first thing that is done using the Tsukamoto method is to make the process of combining 9 fuzzy sets as follows: Decreasing demand, Fixed demand, Increasing demand, Low supply, Medium inventory, Decreasing delivery of goods, Fixed goods delivery and Increasing goods shipments and determining crisp output. In the existing condition of Alfamidi minimarkets with 2 liter Sunco products, the demand for shipping goods is always excessive. So that in the Tsukamoto method, each consequent in the IF-THEN form must be represented by a fuzzy set with a monotonous membership function. As a result, the inference result of each rule is given crisp based on the α-predicate (fire strength). The final result uses a weighted average. So that it can be analyzed the stock of 2 liter packaged Sunco cooking oil that must be sent in November, namely 673 packs.